The Prospects of Swietenia macrophylla King in Skin Care - Camille, Keisha Mahendra; Goh, Khang Wen; Long, Chiau Ming *; Zengin, Gokhan; Low, Liang Ee; Ser, Hooi Leng *; Goh, Bey Hing * (MDPI, 2022)
The importance of cosmetics in our lives is immeasurable. Covering items from daily personal hygienic products to skincare, it has become essential to consumers that the items that they use are safe and effective. Since natural products are from natural sources, and therefore considered "natural" and "green" in the public's eyes, the rise in demand for such products is not surprising. Even so, factoring in the need to remain on trend and innovative, cosmetic companies are on a constant search for new ingredients and inventive new formulations. Based on numerous literature, the seed of Swietenia macrophylla has been shown to possess several potential "cosmetic-worthy" bioproperties, such as skin whitening, photoprotective, antioxidant, antimicrobial, etc. These properties are vital in the cosmetic business, as they ultimately contribute to the "ageless" beauty that many consumers yearn for. Therefore, with further refinement and research, these active phytocompounds may be a great contribution to the cosmetic field in the near future.